Managing non-target wildlife mortality whilst using rodenticides to eradicate invasive rodents on islands - Paula A. Castaño; Karl J. Campbell; Greg S. Baxter; Victor Carrión; Francesca Cunninghame; Penny Fisher; Richard Griffiths; Chad C. Hanson; Gregg R. Howald; Wesley J. Jolley; Bradford S. Keitt; Pete J. McClelland; et al. (Biological Invasions, 2022)

Relative palatability and efficacy of brodifacoum-25D conservation rodenticide pellets for mouse eradication on Midway Atoll - Peter J. Kappes; Shane R. Siers; Israel L. Leinbach; Robert T. Sugihara; Wesley J. Jolley; Jonathan H. Plissner; Elizabeth N. Flint; Kelly L. Goodale; Gregg R. Howald (Biological Invasions, 2022)
Invasive mice ( Mus spp.) can negatively impact island species and ecosystems. Because fewer island rodent eradications have been attempted for mice compared to rats ( Rattus spp.), less is known about efficacy and palatability of rodenticide baits for mouse eradications. We performed a series of bait acceptance and efficacy cage trials using a standard formulation of brodifacoum-based rodenticide on wild-caught mice from Sand Island, Midway Atoll, to help inform a proposed eradication there. Mice were offered ad libitum brodifacoum pellets along with various alternative food sources, and a “no choice” treatment group received only bait pellets. Mortality in the no choice trial was 100%; however, when offered alternative foods, mice preferred the alternative diets to the bait, leading to low mortality (40%). Because there was concern that the bittering agent Bitrex® in the formulation may have reduced palatability, we conducted a subsequent trial comparing brodifacoum bait with and without Bitrex. Mortality in the with-Bitrex treatment group was slightly higher, indicating that the bittering agent was not likely responsible for low efficacy. Laboratory trials cannot account for the numerous environmental and behavioral factors that influence bait acceptance nor replicate the true availability of alternative food sources in the environment, so low efficacy results from these trials should be interpreted cautiously and not necessarily as a measure of the likelihood of success or failure of a proposed eradication.

International consensus principles for ethical wildlife control - Sara Dubois; Nicole Fenwick; Erin A. Ryan; Liv Baker; Sandra E. Baker; Ngaio J. Beausoleil; Scott Carter; Barbara Cartwright; Federico Costa; Chris Draper; John Griffin; Adam Grogan; et al. (Conservation Biology, 2017)
Human–wildlife conflicts are commonly addressed by excluding, relocating, or lethally controlling animals with the goal of preserving public health and safety, protecting property, or conserving other valued wildlife. However, declining wildlife populations, a lack of efficacy of control methods in achieving desired outcomes, and changes in how people value animals have triggered widespread acknowledgment of the need for ethical and evidence‐based approaches to managing such conflicts. We explored international perspectives on and experiences with human–wildlife conflicts to develop principles for ethical wildlife control. A diverse panel of 20 experts convened at a 2‐day workshop and developed the principles through a facilitated engagement process and discussion. They determined that efforts to control wildlife should begin wherever possible by altering the human practices that cause human–wildlife conflict and by developing a culture of coexistence; be justified by evidence that significant harms are being caused to people, property, livelihoods, ecosystems, and/or other animals; have measurable outcome‐based objectives that are clear, achievable, monitored, and adaptive; predictably minimize animal welfare harms to the fewest number of animals; be informed by community values as well as scientific, technical, and practical information; be integrated into plans for systematic long‐term management; and be based on the specifics of the situation rather than negative labels (pest, overabundant) applied to the target species. We recommend that these principles guide development of international, national, and local standards and control decisions and implementation.

Passive recovery of an island bird community after rodent eradication - Donald A. Croll; Kelly M. Newton; Matthew McKown; Nick Holmes; Jeffrey C. Williams; Hillary S. Young; Stacey Buckelew; Coral A. Wolf; Gregg Howald; Milagra F. Bock; Jennifer A. Curl; Bernie R. Tershy (Biological Invasions, 2016)

Severity of the Effects of Invasive Rats on Seabirds: A Global Review - HOLLY P. JONES; BERNIE R. TERSHY; ERIKA S. ZAVALETA; DONALD A. CROLL; BRADFORD S. KEITT; MYRA E. FINKELSTEIN; GREGG R. HOWALD (Conservation Biology, 2008)
Invasive rats are some of the largest contributors to seabird extinction and endangerment worldwide. We conducted a meta‐analysis of studies on seabird–rat interactions to examine which seabird phylogenetic, morphological, behavioral, and life history characteristics affect their susceptibility to invasive rats and to identify which rat species have had the largest impact on seabird mortality. We examined 94 manuscripts that demonstrated rat effects on seabirds. All studies combined resulted in 115 independent rat–seabird interactions on 61 islands or island chains with 75 species of seabirds in 10 families affected. Seabirds in the family Hydrobatidae and other small, burrow‐nesting seabirds were most affected by invasive rats. Laridae and other large, ground‐nesting seabirds were the least vulnerable to rats. Of the 3 species of invasive rats, Rattus rattus had the largest mean impact on seabirds followed by R. norvegicus and R. exulans; nevertheless, these differences were not statistically significant. Our findings should help managers and conservation practitioners prioritize selection of islands for rat eradication based on seabird life history traits, develop testable hypotheses for seabird response to rat eradication, provide justification for rat eradication campaigns, and identify suitable levels of response and prevention measures to rat invasion. Assessment of the effects of rats on seabirds can be improved by data derived from additional experimental studies, with emphasis on understudied seabird families such as Sulidae, Phalacrocoracidae, Spheniscidae, Fregatidae, Pelecanoididae, Phaethontidae, and Diomedeidae and evaluation of rat impacts in tropical regions.

Invasive Rodent Eradication on Islands - GREGG HOWALD; C. JOSH DONLAN; JUAN PABLO GALVÁN; JAMES C. RUSSELL; JOHN PARKES; ARACELI SAMANIEGO; YIWEI WANG; DICK VEITCH; PIERO GENOVESI; MICHEL PASCAL; ALAN SAUNDERS; BERNIE TERSHY (Conservation Biology, 2007)
Invasive mammals are the greatest threat to island biodiversity and invasive rodents are likely responsible for the greatest number of extinctions and ecosystem changes. Techniques for eradicating rodents from islands were developed over 2 decades ago. Since that time there has been a significant development and application of this conservation tool. We reviewed the literature on invasive rodent eradications to assess its current state and identify actions to make it more effective. Worldwide, 332 successful rodent eradications have been undertaken; we identified 35 failed eradications and 20 campaigns of unknown result. Invasive rodents have been eradicated from 284 islands (47,628 ha). With the exception of two small islands, rodenticides were used in all eradication campaigns. Brodifacoum was used in 71% of campaigns and 91% of the total area treated. The most frequent rodenticide distribution methods (from most to least) are bait stations, hand broadcasting, and aerial broadcasting. Nevertheless, campaigns using aerial broadcast made up 76% of the total area treated. Mortality of native vertebrates due to nontarget poisoning has been documented, but affected species quickly recover to pre‐eradication population levels or higher. A variety of methods have been developed to mitigate nontarget impacts, and applied research can further aid in minimizing impacts. Land managers should routinely remove invasive rodents from islands Mus musculus ), island size may no longer be the limiting factor for rodent eradications; rather, social acceptance and funding may be the main challenges. To be successful, large‐scale rodent campaigns should be integrated with programs to improve the livelihoods of residents, island biosecurity, and reinvasion response programs.